Detecting precursory patterns to enhance earthquake prediction in Chile. (March 2015) - Florido, E.; Martínez-Álvarez, F.; Morales-Esteban, A.; Reyes, J.; Aznarte-Mellado, J.L.
Abstract: The prediction of earthquakes is a task of utmost difficulty that has been widely addressed by using many different strategies, with no particular good results thus far. Seismic time series of the four most active Chilean zones, the country with largest seismic activity, are analyzed in this study in order to discover precursory patterns for large earthquakes. First, raw data are transformed by removing aftershocks and foreshocks, since the goal is to only predict main shocks. New attributes, based on the well-known b -value, are also generated. Later, these data are labeled, and consequently discretized, by the application of a clustering algorithm, following the suggestions found in recent literature. Earthquakes with magnitude larger than 4.4 are identified in the time series. Finally, the sequence of labels acting as precursory patterns for such earthquakes are searched for within the datasets. Results verging on 70% on average are reported, leading to conclude that the methodology proposed is suitable to be applied in other zones with similar seismicity. Highlights: Discovery of precursory patterns for medium-large earthquakes in Chile. b-value's ability to predict earthquakes is confirmed. General purpose methodology: can be applied to any other area. Accuracy rate above 70%.